Jihad and Social Change - Awaludin, Taufik (Asyahid Journal of Islamic and Quranic Studies (AJIQS), 2023)
Knowledge or understanding as well as insight into Islam is very necessary as a foundation for being a Muslim, because quite a few among Muslims and the existence of Western propaganda to attack Islam, both of these things make Muslims and non-Muslims currently misunderstand the concept of Jihad. The jihad shown today is identified with people who are bloodthirsty to spread Islam with the sword. This research aims to answer questions about 1) Was Islam spread not through violence? 2) Is Jihad a war of defense? 3) Is Jihad an approach to Da'wah? The linguistic meaning of jihad is general, namely hard work. The Al-Quran has directed the meaning of jihad to a more specific meaning, namely devoting all one's energy, wealth and thoughts to fighting in the way of Allah, either directly or by spending possessions, opinions, increasing logistics, etc. Thus, the more appropriate meaning of jihad taken by Muslims is to fight in the way of Allah against oneself and unbelievers in order to elevate the word of Allah. Keywords: Islam, jihad, war, Western propaganda.   Abstrak Pengetahuan atau pemahaman juga wawasan tentang Islam sangat diperlukan sebagai pondasi sebagai muslim, karena tidak sedikit diantara kaum muslimin dan adanya propaganda-propaganda Barat untuk menyerang Islam, kedua hal tersebut menjadikan kaum muslimin dan orang-orang non muslim saat ini salah memahami konsep Jihad. Jihad yang ditampilkan saat ini diidentikkan dengan orang yang haus darah untuk menyebarkan Islam dengan pedang. Penelitian ini bertujuan untuk menjawab pertanyaan tentang 1) Apakah Islam Disebarkan Bukan Dengan kekerasan? 2) Apakah Jihad merupakan perang defensi? 3) Apakah Jihad merupakan pendekatan Dakwah? Makna jihad secara bahasa bersifat umum, yaitu kerja keras. Al-Quran telah mengarahkan makna jihad pada arti yang lebih spesifik, yaitu mencurahkan segenap tenaga, harta juga pikiran untuk berperang di jalan Allah, baik langsung maupun dengan cara mengeluarkan harta benda, pendapat, memperbanyak logistik, dan lain-lain. Dengan demikian, makna jihad yang lebih tepat diambil oleh kaum Muslim adalah berperang di jalan Allah melawan diri sendiri serta orang-orang kafir dalam rangka meninggikan kalimat Allah. Kata kunci: Islam, jihad, perang, propaganda Barat